Urgensi Pengesahan Undang-Undang Penilai Sebagai Instrumen Pendukung Pelaksanaan Proyek Strategis Nasional (PSN) dalam Konteks Pengadaan Tanah untuk Pembangunan Jalan Tol (Highway): Penelitian - Effendri Rais; Ibnu Syurkron Alfaher; Riska Rahmawat; Ika Vaouziah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Article 33 paragraph (3) of the 1945 Constitution mandates that natural resources must be used to the greatest extent possible for the prosperity of the people, which is implemented through various regulations, including in land acquisition for National Strategic Projects (PSN) such as toll roads. In this process, the appraiser profession is crucial in determining fair compensation. Currently, the appraiser profession in Indonesia is only regulated by ministerial-level regulations, which differs from other countries that already have specific laws. The absence of this law results in weak enforcement of ethics, a lack of legal protection, and a high risk of intervention that threatens the independence of appraisers. Therefore, the drafting of a Law on Appraisers is very urgent. The existence of this law will create a professional, transparent, and accountable appraisal system, as well as strengthen the integrity of the profession and support the success of national strategic projects.